High-Yield Cellulose Hydrolysis Using Silica-Amino Methanesulfonic Acid Catalyst: Hidrolisis Selulosa Hasil Tinggi Menggunakan Katalis Asam Metanesulfonat Silika-Amino - Hussein Apdel Bari Zuwaid (Academia Open, 2025)
General Background: The increasing demand for sustainable energy sources has driven interest in replacing fossil fuels with biofuels. Specific Background: Second-generation bio-refining technologies utilizing lignocellulosic biomass offer a promising path toward environmentally and economically viable biofuel production. Knowledge Gap: However, efficient catalytic systems for cellulose hydrolysis under mild conditions remain limited. Aims: This study aims to synthesize and evaluate a heterogeneous catalyst, Silica-Amino methanesulfonic acid, for effective cellulose hydrolysis into glucose. Results: The catalyst, synthesized via one-pot and reflux methods, achieved up to 88% hydrolysis yield at 130 °C within 6 hours. The one-pot method yielded a 4.2 g catalyst with slightly superior activity. Optimal conditions were determined as 0.1 g catalyst mass and 130 °C. Solvent screening revealed that DMF/LiCl and Cyclohexanol/LiCl mixtures were most effective. Novelty: The direct (one-pot) synthesis method produced a catalyst with comparable or superior performance to traditional reflux methods, highlighting a more efficient and scalable approach. Implications: These findings demonstrate the potential of Silica-Amino methanesulfonic acid as a robust and reusable catalyst for bio-refining processes, contributing to the advancement of green chemistry and sustainable fuel alternatives. Highlights: Catalyst achieved 88% glucose yield from cellulose. One-pot synthesis more efficient than reflux. DMF/LiCl best solvent for hydrolysis process. Keywords: Biofuels, Cellulose Hydrolysis, Heterogeneous Catalyst, Silica-Amino Methanesulfonic Acid, Lignocellulosic Biomass